Design of Square Waveguide Corner - Hnilička, Tomáš; Schejbal, Vladimír; Fišer, Ondřej; Zálabský, Tomáš (Slovenská elektrotechnická spoločnosť, 2018)
The paper presents a full-wave design for matching a square mitered waveguide corner. We compare the full-wave numerical simulations with experimental results. The corner can operate with both polarizations, i.e. TE10 for H-plane bend and TE01 for E-plane bend. That is very useful for intended meteorological radar. That could use dual polarization transmit and receive both horizontal and vertical polarizations to assess additional properties of the weather targets.
Návrh pravoúhlého vlnovodného ohybu s čtvercovým průřezem
Keywords: Corner design; design optimization; dual-mode waveguide; full-wave design; meteorological radar; square waveguide; waveguide corner; Návrh pravoúhlého vlnovodu; Čtvercový vlnovod; Vlnovod pro obě polarizace; Meteorologický radar